What do autistic children who are interested in letters and numbers do with them? A qualitative study - Alexia Ostrolenk; Mélanie Boisvert; Laurent Mottron (International Journal of Qualitative Studies on Health & Well-Being)
Purpose Over a third of autistic children exhibit an intense or exclusive interest in letters and numbers at the time of diagnosis. This article aims to qualitatively investigate the atypical manifestations of this interest in autism compared to typically developing children and determine if and how it can benefit children and their families. Methods The participants were the parents of 138 autistic children (84% were non-speaking or minimally speaking) and 76 typically developing children ages 2–6. They were administered a questionnaire on their child’s interest in letters and numbers, the manifestations of these interests, the parental attitude towards it, and the child’s oral language. An inductive thematic analysis was performed on the qualitative data to establish recurring themes. Results Eight themes were identified: atypical behaviours related to written material, emotional attachment to letters and numbers, language acquisition, use of screens, solitary behaviour, reduction of the interest over time, parental attitudes, and other special abilities. Conclusion This study reveals that the interest in written material manifests itself in atypical ways in autism and is not comparable to the development of an interest in reading in a typically developing context. This interest also presents multiple beneficial aspects for children and their families.